Portfolio Preferences of Foreign Institutional Ivestors - Aggarwal, Reena; Klapper, Leora; Wysocki, Peter D. (World Bank, Washington, DC, 2014)
The authors examine the relationship between foreign investment and the attributes of emerging market countries and firms in which investment is made. Their findings indicate that countries with higher levels of economic development and floating exchange rate regimes tend to have greater ability to obtain foreign capital. After controlling for the country's level of economic development, they find that firms in countries with stronger shareholder rights and legal framework attract more foreign capital. The authors also find that foreign institutions allocate more of their assets to firms with better corporate governance after controlling for other country and firm attributes. The main firm-level measures of corporate governance are derived from accounting quality variables. Their results imply that steps can be taken both at the country and the firm level to create an environment conducive to foreign portfolio investment. The analysis is based on a unique dataset consisting of equity positions of U.S. mutual funds in emerging markets.